SECONDARY SCHOOL TEACHERS’ PERSPECTIVES ON AUTHORSHIP ANALYSIS IN THE CONTEXT OF AI-PLAGIARISM ON STUDENTS’ WORKS IN ENGLISH LESSONS - Suni, Fauziyyah Mufida; Maulidya, Rizka; Putri, Annisa Wahyu Dwi (UHN IGB Sugriwa Denpasar, 2025)
The rapid integration of Artificial Intelligence (AI) into educational environments has created new challenges for maintaining academic integrity, particularly concerning AI-assisted student work. As traditional plagiarism-detection tools prove insufficient against sophisticated AI-generated content, there is a growing need to explore teacher-driven detection strategies. This descriptive qualitative study addresses this gap by investigating teachers’ views on using authorship analysis as a method to identify AI-generated content in student assignments. The research utilised semi-structured interviews with ten secondary school teachers specialising in the English language. Data were analysed using thematic analysis. The findings revealed three primary themes: (1) The ELT Vulnerability to AI, highlighting an increasing concern about AI-assisted plagiarism in English language teaching; (2) The Resource Gap, where teachers express a lack of sufficient training and institutional resources to address the challenge effectively; and (3) The suggestion to combine AI detection tools, manual authorship analysis, and conversations with students as a strategy. The study highlights how institutional policies and the specific local educational context influence teachers' attitudes toward AI and academic integrity. There is a need to establish clear AI policies and promote AI literacy to students.